Carnosine Stimulates Macrophage-Mediated Clearance of Senescent Skin Cells Through Activation of the AKT2 Signaling Pathway by CD36 and RAGE - Li, Xuenan; Yang, Kaiye; Gao, Shuang; Zhao, Jungang; Liu, Guangrong; Chen, Yu; Lin, Haojie; Zhao, Wengang; Hu, Zhenlin; Xu, Nuo (Frontiers in Pharmacology, 2020)
Background: Macrophages can selectively recognize and eliminate senescent cells, but this function is impaired with age, resulting in excessive accumulation of senescent cells in the skin, which ultimately causes skin aging. Therefore, enhancing the immune surveillance ability of macrophages to clear senescent keratinocytes and fibroblasts from aging skin may be an effective skin rejuvenation strategy. Methods: In this study, a macrophage and senescent skin cell co-culture model was established whereby THP-1-derived macrophages and tert-butyl hydroxide-induced senescent skin cells (HaCaT and HFF-1) were grown in the same culture. Senescent skin cells were detected by the SPiDER-βgal assay, and the expression of secretory phenotype factors related to senescence was assayed by qPCR. The effect of carnosine on the number of SA-β-gal positive skin cells in the macrophage-senescent skin cell co-culture was evaluated and compared with that in the senescent skin cell monoculture. Results: Carnosine promoted macrophage-mediated elimination of senescent skin cells in the co-culture. Through the AKT2 signaling pathway, carnosine upregulated the expression of CD36 and receptors for advanced glycation end products and elevated the phagocytic capacity of the macrophages, thereby promoting the ability of the macrophages to eliminate the senescent skin cells. Conclusion: Carnosine could boost the immune surveillance ability of macrophages to clear senescent keratinocytes and fibroblasts in the macrophage-senescent skin cell co-culture by activating the AKT2 signaling pathway, suggesting the possibility of using carnosine as an agent to reverse skin aging.